EXPLORING THE POTENTIAL OF AGRO-TOURISM FOR SUSTAINABLE RURAL DEVELOPMENT IN THE KASHMIR VALLEY, INDIA - Asif Bashir; Naseer Ahmad Bhat; Shagufta Mohi Ud Din; Azra Mushtaq (CV. Radja Publika, 2024)
Agro-tourism, the fusion of agriculture and tourism, is emerging as a viable strategy for rural development, especially in regions with rich agricultural heritage and scenic landscapes. This paper explores the potential of agro-tourism in the Kashmir Valley, a region known for its fertile land, traditional farming practices, and natural beauty. The study highlights the economic, social, and environmental benefits of agro-tourism, such as income diversification for farmers, job creation, and environmental sustainability. It also addresses the challenges that hinder the development of agro-tourism in Kashmir, including inadequate infrastructure, political instability, limited awareness among farmers, and environmental concerns. The paper emphasizes the need for strategic investments in infrastructure, farmer education, and effective marketing to promote the Kashmir Valley as a unique agro-tourism destination. Additionally, it discusses the importance of public-private sector collaboration and policy support to foster growth in the sector. Through sustainable practices and the preservation of local culture and traditions, agro-tourism in Kashmir can contribute to rural development, empower local communities, and provide an authentic experience for tourists. The findings suggest that with careful planning and execution, agro-tourism has the potential to play a significant role in revitalizing the region’s economy while promoting environmental conservation and cultural heritage.